Global ecological predictors of the soil priming effect - Bastida, Felipe; García, Carlos; Fierer, Noah; Eldridge, David J.; Bowker, Matthew A.; Abades, Sebastián; Alfaro, Fernando D.; Asefaw Berhe, Asmeret; Cutler, Nick A.; Gallardo, Antonio; García-Velázquez, Laura; Hart, Stephen C.; et al. (Nature communications, 2019)
Identifying the global drivers of soil priming is essential to understanding C cycling in terrestrial ecosystems. We conducted a survey of soils across 86 globally-distributed locations, spanning a wide range of climates, biotic communities, and soil conditions, and evaluated the apparent soil priming effect using 13 C-glucose labeling. Here we show that the magnitude of the positive apparent priming effect (increase in CO 2 release through accelerated microbial biomass turnover) was negatively associated with SOC content and microbial respiration rates. Our statistical modeling suggests that apparent priming effects tend to be negative in more mesic sites associated with higher SOC contents. In contrast, a single-input of labile C causes positive apparent priming effects in more arid locations with low SOC contents. Our results provide solid evidence that SOC content plays a critical role in regulating apparent priming effects, with important implications for the improvement of C cycling models under global change scenarios. The global ecological predictors of soil priming remain unclear. Here the authors conducted a global survey of soils from 86 global locations using an isotopic approach and find that in more mesic sites with high SOC concentrations, soil priming effects are more likely to be negative.